The Dark Side of Organizational Identification: A Multi-Study Investigation of Negative Outcomes - Irshad, Muhammad; Bashir, Sajid (Frontiers in Psychology, 2020)
After more than two decades of research on the positive side of organizational identification, researchers have begun to realize that there is a dark side to it that needs immediate consideration. With support from social identity theory, the current study sheds light on this understudied role of the dark side of organizational identification by investigating its indirect effect on (a) psychological entitlement, (b) unethical pro-organizational behavior, and (c) pro-social rule-breaking through externally motivated organizational citizenship behavior and taking leader-member exchange as a boundary condition. This study conducted two surveys to test the proposed moderated mediation model. Data for the first study was collected from employees (N=356) working in the service sector, whereas responses for study 2 were taken from employees (N=259) working in the hospitality industry. Time lagged research design was selected for both the surveys to avoid common method bias. The results proved that organizational identification causes adverse outcomes in the form of psychological entitlement, pro-organizational rule breaking, and unethical pro-organizational behavior through externally motivated organizational citizenship behavior. Furthermore, a high-quality leader-member exchange relationship enhances these indirect effects of organizational identification on its outcomes. Several theoretical and practical implications, along with limitations and future research directions, are also discussed.